2010
DOI: 10.1002/biof.109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resveratrol on endothelial cell function: Molecular mechanisms

Abstract: The polyphenolic natural product resveratrol (RV), best known for its occurrence in grape skin and red wine, is considered a candidate drug for prevention and treatment of cardiovascular diseases. This review aims to summarize the molecular effects of RV on endothelial cells, which line the inner walls of blood vessels and play a key role in the development of those diseases. We describe how RV enhances endothelial nitric oxide production, improves endothelial redox balance and inhibits endothelial activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 79 publications
0
45
0
Order By: Relevance
“…5,6,9,10 Part of this benefit is because of an improvement of endothelial dysfunction through different molecular pathways that include enhanced endothelial nitric oxide production and vasodilatation, improved redox balance and anti-inflammatory mechanisms. 34,35 Although circulating biomarkers cannot fully capture the complexity of paracrine regulations in the endothelium, we found that light-to-moderate wine consumption was associated with a dose-dependent reduction in the plasma concentration of a stable precursor of endothelin-1. This highly potent vasoconstrictor peptide, when elevated, is a strong predictor of bad outcome in chronic HF.…”
Section: Wine Consumption and Circulating Biomarkersmentioning
confidence: 80%
“…5,6,9,10 Part of this benefit is because of an improvement of endothelial dysfunction through different molecular pathways that include enhanced endothelial nitric oxide production and vasodilatation, improved redox balance and anti-inflammatory mechanisms. 34,35 Although circulating biomarkers cannot fully capture the complexity of paracrine regulations in the endothelium, we found that light-to-moderate wine consumption was associated with a dose-dependent reduction in the plasma concentration of a stable precursor of endothelin-1. This highly potent vasoconstrictor peptide, when elevated, is a strong predictor of bad outcome in chronic HF.…”
Section: Wine Consumption and Circulating Biomarkersmentioning
confidence: 80%
“…Yet more mechanisms of action have been proposed but these become evident only after prolonged exposure to t-Resv: for example, activation of silent mating type information regulation 2 homolog (SIRT1) can promote direct deacetylation of eNOS [20]. Discussion of the diverse mechanisms proposed to explain how t-Resv might enhance endothelial activity and NO production can be found at greater depth in [17].…”
Section: Introductionmentioning
confidence: 96%
“…Other reports have also shown that t-Resv may increase NO availability by interfering with the generation of reactive oxygen species (ROS) [16,17]. It has also been suggested that t-Resv enhances endothelial nitric oxide synthase (eNOS) activity via 5 0 adenosine monophosphate-activated protein kinase (AMPK)-or extracellular signal-regulated kinase 1/2 (ERK1/2)-mediated phosphorylation at Ser 1177 [18,19].…”
Section: Introductionmentioning
confidence: 96%
“…FMD was found to be linearly related to log plasma resveratrol concentration. 10 Resveratrol treatment resulted in a dose-related increase in plasma resveratrol and in FMD. 25 Previous cell culture-based studies have shown potential health benefit effects of dietary polyphenols, but such studies typically relied on higher concentrations than those commonly observed in blood following consumption of polyphenol-rich foods or beverages.…”
Section: Hypertensionmentioning
confidence: 98%